Effect of Chloride Ions on Electrochemical Behavior of Canister Materials - Gha-Young Kim; Junhyuk Jang; Minsoo Lee; Jin-Seop Kim (Science and Technology of Nuclear Installations)
Various canister candidate materials (SS316L, Ti-Gr.2, Alloy 22, and Cu) were studied using groundwater at the Korea Atomic Energy Research Institute (KAERI) underground research tunnel (KURT), with the addition of chloride ions using different electrochemical techniques. The corrosion potential and corrosion current of test materials were obtained by the polarization measurement. The polarization measurements revealed that the addition of chloride ions was detrimental to the SS316L and Cu materials by increasing corrosion current, which is an indicator of corrosion rate. Impedance measurements and fitting analysis showed that the corrosion resistance of Cu was more than 10 times lower than that of other materials in the KURT groundwater solution containing 0.1 M of chloride ions.